Pengembangan Chatbot Yanies Cookies Untuk Pemesanan Kue Kering Berbasis Dialogflow - Sultan Saladdin; Issa Arwani; Bayu Rahayudi (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2020)
Cookies are one of the most sought-after gifts by the public. Ahead of the Eid holiday, Yanies Cookies are overwhelmed in fulfilling orders that come. Therefore, Yanies Cookies requires customer service that can help in ordering cookies. This service was eventually developed into Chatbot. Chatbot Yanies Cookies developed with prototyping metode. Chatbot was developed with Dialogflow as a program to develop dynamic and doesn't need to handling the conversations needed to manage natural languages processing. Python and Flask framework are programming languages ​​that are used to develop the middleware APIs using webhook. The Middleware API working as a bridge integrating Dialogflow and Google App Engine (GAE) where the Chatbot application is run by GAE which is run on cloud computing. The Google Sheets API is also used in development as an API that is used to help send user order data from Chatbot to the google sheets database. This research resulted in: (1) Chatbot deployed on the Facebook Messenger platform; (2) Chatbot Yanies Cookies Functionality Test consisting of viewing features of cookies menus, ordering cookies, and checking order; (3) Scale the results of the Usability Scale test are used to measure the feasibility score of Chatbot Yanies Cookies based on the results of the respondents' coverage of the respondents. Chatbot Yanies Cookies showed a score of 86 from the range 0-100. Chatbot Yanies Cookies can be accepted as